The Concept of Fitrah, Buya Hamka's Perspective and Its Relationship to the Family Environment: Konsep Fitrah Perspektif Buya Hamka Dan Hubungannya Terhadap Lingkungan Keluarga - Sururim Maudluunah Umar; Dzulfikar Akbar Ramadhan (Universitas Muhammadiyah Sidoarjo, 2022)
This article aims to describe the concept of nature from Buya Hamka's perspective and its relationship to the family environment, so that we can find out what is inside of humans related to doing something, especially things that deviate from the norm. In this study using library research methods with the object of research is the Tafsir Al-Azhar by Buya Hamka and books that discuss the concept of fitrah. The findings in this study are that the role of the environment in the formation of the concept of nature in Buya Hamka's perspective is very important for digging, cleaning and beautifying nature, al-qalb, al-aql and al-jism.